TH3_0FF1C3: um jogo de tabuleiro educacional para o ensino de conceitos da segurança da informação - Schappo, Francis Mallmann (2022)
The current project was developed in line with the Research Development of Educational Technologies in Network, in the Postgraduate Program of Educational Technologies in Network of the Federal University of Santa Maria. Its objective is the development of an educational board game for the application and learning of concepts about information security for people with and without the domain of knowledge. Based on the new General Law for the Protection of Personal Data that came into force for all companies in 2021, and the growing wave of cyberattacks that occur worldwide, the current research tries to answer the question of “An unplugged activity in a could a board game be a facilitator in learning about good Information Security practices?”. The research was applied to computer users for university students with or without experience in the job market. For the development of this work, bibliographic research was carried out, construction of a prototype and application of the board game. Data for analysis were acquired through evaluation questionnaires compiled and demonstrated in the results chapter, where there were positive responses after application as an educational tool to aid in the development of knowledge. The educational board game containing information security knowledge will be an openend product accessible to the entire community in both physical and digital format.